A STUDY OF TEACHER’S PERCEPTIONS ABOUT HAPPINESS CURRICULUM PROGRAM - CLASSES VI -VIII - Sarita,; Dagar, Laxmi (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This paper will emphasize the importance of happiness in the self-satisfaction of an individual particularly children in their lifetime. There are many ways in which one can note and encourage happiness in children and the first one is through mindfulness. There is a marked beneficial correlation between Mindfulness with critical thinking, clarity, problem solving abilities, stress, emotions and attitude of the person. These components provide children with the ability to always approach tasks in a cool and calm manner thus making them happy individuals. On the same note, awareness of other virtues inclusively, forgiveness, dignity of work, helpfulness, empathy, trust, patience, honesty, hard-working culture, responsibilities, and gratitude develops the kind of personalities emotionally and socially needed by children. These aspects not only make one happy but also nurture a good character and moral person. The love between family and friends is also a critical aspect in determining the level of happiness of a child. Punctuality, peer relations, respect for children and elders together with the maintenance of family values make children better manage their behaviors and have positive attitudes towards life milestones. Love and cooperation with others and the ability to know what the true definition of happiness is being healthy, cheerful and the presence of many other factors such as sharing and caring are part and parcel of personified joy. When children experience positive interactions and a positive environment during childhood, then they are likely to develop a balanced personality and perception about life and this makes them grow up to become emotionally and intelligent individuals. Teachers being caretakers of students are in an ethical capacity to bring ‘positivity’ in the lives of children. Positive education which is a relatively novel idea in psychology focuses on achievement of positive subjective states in the learning process. This paper aims to focus on the function of teachers in the pursuit of happiness of children, including analyzing the lessons learnt from ‘Happiness Curriculum’ launched by the Delhi government. From this, the paper suggests that for the holistic aspect of education, the government should embrace all the aspects and dimensions of learning and well-being if children are to be happy.